Epidemiology of pseudoexfoliation syndrome: a hospital based comparative study - Kounsar, Hina; Shaheen, Nusrat; Rather, Suhail R. (International Journal of Research in Medical Sciences, 2018)
Background: Pseudoexfoliation syndrome (PEX), is an age-related condition with generalized disorder of the extracellular matrix (ECM) characterized by a pathological accumulation of polymorphic fibrillar extracellular material in ocular tissue and various visceral organs. The search for the etiology of pseudoexfoliation syndrome has been directed towards both genetic and environmental factors. It is associated with many ocular and systemic complications. Methods: The study was a hospital based comparative clinical study with 100 consecutive patients with pseudoexfoliation and age and sex matched 100 patients as control without pseudoexfoliation. The patients were registered on a Pre-structured Proforma which included patients’ demographic detail, history and examination. Examination protocol including visual acuity with snellen’s chart for literate patients and E-Chart for illiterate patients, intraocular pressure (by Goldmann applanation tonometry), slit lamp examination and fundus examination. Results: The mean age of cases was 65.93± 7.82 years ranging from 49 to 85 years. The mean age of controls was 63.98± 7.06 years ranging from 50 to 80 years (p=0.139). 72% of cases were more than 60 years old. Male female ratio was 1.63:1. Most of the cases were from Budgam, Bandipora and Ganderbal areas. Spring water was proportionately more frequently used as water source in cases (χ2 =18.5, p=0.000), and tube well water in controls. The mean duration of smoking was 26.63±24.74 pack years for cases and 14.88±17.10 pack years for controls (p=0.000). Average duration of daytime exposure for cases was 6.68±2.13 hours and for controls it was 4.52±2.53 hours. Among cases 12 patients (12%) were on treatment for glaucoma whereas among controls, 1 patient (1%) was on treatment for glaucoma. With respect to dietary habits, there was no difference between cases and controls. Farmers comprised of 49% of cases, followed by House wives and government employees. Conclusions: The study concludes that PEX is very common in our region, increasing with age and more in men. Smoking, occupations involved with sunlight exposure, spring water as water source are possible risk factors for PEX. Glaucoma and cataract are common ocular complications of the syndrome.